Z for Zachariah - O'Brien, Robert C. (Simon Pulse, 2007)
Seemingly the only person left alive after a nuclear war, a sixteen-year-old girl is relieved to see a man arrive into her valley until she realizes that he is a tyrant and she must somehow escape.